Variabel yang memengaruhi keputusan investasi pasar modal pegawai swasta di kota jakarta selatan - Hermawan, Ricard; Muhammad, Maulana Malik; Iskandar, Donant Alananto (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
The effect of financial literacy, financial behavior, and risk tolerance on investment decisions among private sector employees in South Jakarta City was researched in this study. Questionnaires are used to collect data for research. This research model uses a quantitative approach survey with a purposive sampling method to analyze 107 private sector employees in South Jakarta City. SPSS Version 26 is used for data analysis, which includes multiple linear regression and hypothesis testing. The findings reveal that financial literacy, financial behavior, and risk tolerance all have a positive and significant influence on the capital market investment decisions of private sector employees in South Jakarta City.